Choice as an engine of independence : implications for employee voice and managerial decision making - Nanakdewa, Kevin (Nanyang Technological University, 2020)
Past research on choice has primarily conceptualized choice as an objective construct. For example, people can either have a choice or not, or people can have more versus fewer alternatives to select from. In the present paper, I extended an emerging stream of research on the “choice mindset”, which highlights the subjective aspect of choice. Research on the choice mindset found that even when people engaged in the same behaviors, the extent to which they construed their actions as choices varied greatly. In chapter 1, I integrated the findings from existing research to identify two novel psychological mechanisms through which choice influences outcomes: (1) choice leads to a greater emphasis on personal agency and freedom, and (2) choice is associated with analytic cognition – a tendency to focus on objects independent of the broader context. Consistent with the first psychological mechanism of choice, chapter 2 found that a choice mindset led people to a greater awareness and experience of independence in Singapore, the US, and India. The findings suggest that choice may be an unmarked engine of growing global individualism. Chapter 3, consistent with the second psychological mechanism of choice, found that a choice mindset led people to exhibit greater cognitive flexibility, thereby reducing bias in decision making and improving their outcomes. The research presented in this thesis is the first to document a heightened sense of independence as a key outcome of choice, and the first research to demonstrate that choice can influence decision making biases (e.g., the sunk-cost bias).